2013
DOI: 10.2458/azu_js_rc.55.16132
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Sedimentary Organic Carbon Storage and Turnover of Tidal Mangrove Stands in Southern China Based on Carbon Isotopic Measurements

Abstract: ABSTRACT. Mangrove ecosystems are highly productive and play an important role in tropical and global coastal carbon (C) budgets. However, sedimentary organic carbon (SOC) storage and turnover in mangrove forests are still poorly understood. Based on C isotopic measurements of sediment cores of 2 mangrove stands in southern China, SOC density was 431.77 Mg ha -1 at site 1 (a Aegiceras corniculatum-dominated high tidal stand) and 243.65 Mg ha -1 in site 2 (a Bruguiera gymnorrhiza + Kandelia candel-dominated mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The agricultural soils include profiles from Taiwan and Luzon (Becker‐Heidmann et al, ). The forest (Ding et al, ; Shen, Sun, et al, ; Shen, Yi, et al, ; Shen et al, ) and mangrove (Zhang et al, ; Zhang et al, ) soil profiles and paleosols (Ding et al, ) all come from mainland China. Fluvial sediments include Zhujiang River (Gao et al, ; Liu et al, ; Tao et al, ; Wei, Shen, et al, ; Wei, Yi, et al, ) and southwestern Taiwanese rivers (Kao et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The agricultural soils include profiles from Taiwan and Luzon (Becker‐Heidmann et al, ). The forest (Ding et al, ; Shen, Sun, et al, ; Shen, Yi, et al, ; Shen et al, ) and mangrove (Zhang et al, ; Zhang et al, ) soil profiles and paleosols (Ding et al, ) all come from mainland China. Fluvial sediments include Zhujiang River (Gao et al, ; Liu et al, ; Tao et al, ; Wei, Shen, et al, ; Wei, Yi, et al, ) and southwestern Taiwanese rivers (Kao et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the speed and ease of carbon mineralization depend on the OM fraction in which it resides; for example, humus-carbon mineralizes slowly when compared to plant residue, particulate OM, and soil microbial biomass [41]. The tidal process is one factor driving a great influx of SOC content and turnover in mangrove forests [42].…”
Section: Discussion and Comparisonsmentioning
confidence: 99%
“…Carbon sequestration is an important service that has recently been addressed by several authors (see Duke et al 2007;Alongi 2012;Chen et al 2012b;Donato et al 2012;Matsui et al 2012;Bashan et al 2013;Rivera-Monroy et al 2013;Winterwerp et al 2013;Zhang et al 2013). At a global level Giri et al (2011) reported that mangroves had the capacity to sequester approximately 22.8 million metric tons of carbon each year.…”
Section: Mangrove Ecosystem Services In the Rehabilitation Literaturementioning
confidence: 99%